Distributed rendezvous and tracking for multiple unicycles with heterogeneous input disturbances. (21st February 2017) - Yang, Chengshuai; Chen, Fei; Xiang, Linying; Lan, Weiyao
Summary: This paper addresses the distributed rendezvous and tracking problems for multiple unicycles in the presence of unknown heterogeneous disturbances. Disturbance compensators are designed to attenuate the effect of unknown disturbances, which rely on a state estimator constructed to estimate the disturbance‐free states of the controlled agents. LaSalle's invariance principle and Barbalat's lemma are employed, respectively, to prove the convergence of the systems. For the rendezvous problem, all agents will rendezvous at a pre‐specified point eventually under the effect of input disturbances. For the tracking problem, all follower agents will track the leader agent and then move with the leader at the same linear and angular velocities under the effect of input disturbances. The potential function approach is employed in constructing the control laws that are capable of avoiding inter‐agent collisions. With this method, the tracking error can be made upper bounded while all the agents keep a 'safe' distance from each other. Simulation examples are finally presented to verify the effectiveness of the designed controllers. Copyright © 2017 John Wiley & Sons, Ltd.